2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4550280
|View full text |Cite
|
Sign up to set email alerts
|

Reliability assessment of high temperature lead-free device attach technologies

Abstract: The demand for electronics capable of operating at temperatures above the traditional 125°C limit continues to increase. Devices based on wide band gap semiconductors have been demonstrated to operate at temperatures up to 500°C, but packaging them remains major hurdle to product development. Recent regulations, such as RoHS and WEEE, increase the complexity of the packaging task as they prohibit the use of certain materials in electronic products such as lead, which has traditionally been widely used in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…From these observations it was revealed that the proposed Ag-In TLPS attach material outperformed the DBC substrates during the thermal cycling test. Results obtained from life cycle data (cycles), were comparable to the observed performance of the Pb-rich solder, the most widely used material for high temperature electronics applications [7,21]. When compared with lead-free alternatives, it outperformed technologies such as sintered Ag-nanocolloids as well as sintered Ag nanoparticle pastes [7,21].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…From these observations it was revealed that the proposed Ag-In TLPS attach material outperformed the DBC substrates during the thermal cycling test. Results obtained from life cycle data (cycles), were comparable to the observed performance of the Pb-rich solder, the most widely used material for high temperature electronics applications [7,21]. When compared with lead-free alternatives, it outperformed technologies such as sintered Ag-nanocolloids as well as sintered Ag nanoparticle pastes [7,21].…”
Section: Resultssupporting
confidence: 59%
“…This technique utilizes a reduction of total free energy as the driving force for the sintering reaction. However, this approach has been shown to have reliability limitations [7].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing demand for high power density and high performance power electronics systems, conventional Sn-based solders are no longer considered acceptable for power die attachments or other interconnects where the operating temperature s are expected to rise above 175°C. The use of high lead solders with a Pb content of 85-97 wt.% is a standard and widely accepted approach for improving the reliability of conventional Sn-Ag solder joints [1]. However, lead is restricted in the application of electronics packaging owing to environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…White et al [75] found the main failure distribution in DRAMs has an increasing hazard rate. Quintero et al [76] conducted reliability and life studies on semiconductor diesubstrate assemblies of different sizes under different temperatures. They observed that the Weibull shape parameter was always greater than 1, showing an increasing hazard rate existed rather than a constant hazard rate.…”
Section: Wear-out Periodmentioning
confidence: 99%